2019
DOI: 10.1111/mcn.12712
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of micronutrient powder (MNP) knowledge, coverage, and consumption during the scale‐up of an integrated infant and young child feeding (IYCF‐MNP) programme in Nepal

Abstract: Large‐scale programmes using micronutrient powders (MNPs) may not achieve maximum impact due to limited/inappropriate MNP coverage, consumption, and use. We identify predictors of MNP coverage, maternal knowledge of appropriate use, and child MNP consumption in Nepal. A cross‐sectional survey was conducted in 2,578 mother–child pairs representative of children 6–23 months in two districts that were part of the post‐pilot, scale‐up of an integrated infant and young child feeding‐MNP (IYCF‐MNP) programme. Childr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 36 publications
(77 reference statements)
1
10
0
Order By: Relevance
“…If the aim is for mothers to actively seek out MNP, it is essential that they understand its health benefits. Consistent with other studies, 17,42,44,45 qualitative results from the present study showed that perceived side effects (e.g., diarrhea, vomiting) and change in taste of foods mixed with MNP were among barriers to using MNP. It has been suggested that possible changes to foods due to addition of MNP and the potential negative side effects of MNP should be acknowledged and clearly communicated to caregivers before children start getting MNP.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…If the aim is for mothers to actively seek out MNP, it is essential that they understand its health benefits. Consistent with other studies, 17,42,44,45 qualitative results from the present study showed that perceived side effects (e.g., diarrhea, vomiting) and change in taste of foods mixed with MNP were among barriers to using MNP. It has been suggested that possible changes to foods due to addition of MNP and the potential negative side effects of MNP should be acknowledged and clearly communicated to caregivers before children start getting MNP.…”
Section: Discussionsupporting
confidence: 91%
“…15,16 While MNP interventions have been shown to be efficacious in many studies, they are often conducted in controlled trials using resources that are not usually available during a national implementation or scale-up. 17 In some settings, MNP programs have thus been ineffective due, in part, to factors that may affect actual implementation. 18,19 For example, a study in Uganda 19 found that mothers cooked foods with soda ash to reduce cooking time.…”
Section: Introductionmentioning
confidence: 99%
“…Use of MNP is a long-term preventive intervention that requires continued and sustained practice. Programs should hence both promote new behaviours and sustained practice (D'Agostino et al, 2019) for caretakers to adopt a complex series of behaviours and maintain them (Ford et al, 2019, Locks et al, 2019, Tumilowicz, Habicht, et al, 2019. The behaviours include obtaining sachets initially and over time (coverage) and initiating and continuing to prepare and serve food with MNP to children (sustained intake).…”
Section: The Current Studiesmentioning
confidence: 99%
“…Interesting findings on complication of concurrently setting up two systems for distribution Attention is required to improve access and support continued use-frontline workers are key to support the latter (e.g. they developed a way to bypass the vouchers) related to continued use, as it helped address supply issues, answer questions, discuss issues and provide continued reinforcement (D'Agostino et al, 2019;Locks et al, 2019;Roschnik et al, 2019;Tumilowicz, Habicht, et al, 2019;Tumilowicz, Vossenaar, et al, 2019).…”
Section: Ford Et Al Ugandamentioning
confidence: 99%
See 1 more Smart Citation